Triage in the ICU - Truog, Robert D. (The Hastings Center report, 1992)
Some patients in intensive care units are too sick to derive much benefit from being there, while others are too well to require the technology and skills offered. When ICU resources are scarce, they may ethically be withdrawn from either sort of patient in favor of one more likely to benefit from the care.